A new high frequency MOS-C TOETQO employing DXCCTA. Issue 4 (2nd October 2022) - Laishram, Rubila; Joshi, Manoj; Ranjan, Ashish
ABSTRACT: This research paper reports a high frequency Third Order Electronically Tunable Quadrature Oscillator (TOETQO) using an active element termed as Dual-X Current Conveyor Transconductor Amplifier (DXCCTA) in which active element MOS and passive Capacitor (C) contribute the implementation performance of the proposed design as MOS-C TOETQO. Due to the presence of DXCCTA with active grounded capacitor and MOS-based resistor, the proposed quadrature oscillator facilitates a suitable design for integrated circuits (ICs). The proposed TOETQO circuit produces current as well as voltage outputs simultaneously. Moreover, the non-ideal analysis of the proposed oscillator circuit is also included. The proposed design shows a good agreement for the oscillation criteria due to the acceptable limit of %THD and gives the variation in frequency of oscillation (up to MHz) values with respect to bias current. Moreover, by keeping the bias current constant, frequency of oscillation can also be electronically tuned independently by varying the values of resistor. Finally, Cadence simulation results are depicted to verify the theoretical analyses and practical feasibility of proposed TOETQO design is also well verified with experimental set up by using IC AD844 and CA3080. A fair comparison of the proposed quadrature oscillator with existing literatures is also tabulated.